THE IMMUNOPATHOLOGY OF LIVER GRANULOMAS IN PRIMARY BILIARY CIRRHOSIS - You, Zhengrui (2012)
Liver granuloma are recognized as specific histological features in primary biliary cirrhosis but their significance remains enigmatic. Similarly, there are limited data on the impact of hyper-IgM on granulomas while in both cases a role of B cells has been hypothesized. The present study investigates a significant number of tissue samples from PBC and control livers as well as other granulomatous diseases to investigate the representation of dendritic cells and the role of IgM in PBC-associated granulomas. We demonstrate that the classical cellular marker for dendritc cells CD11c is highly expressed in hepatic granulomas from PBC liver samples, along with markers of immature dendritic cells, i.e. CD11b, low MHC II, IL-23 and CCR7 and CD83 expression, and C1q high expression. PBC patients with granulomas had significantly higher serum IgM levels and PBC granulomas were surrounded by B and plasma cells. Using ad in vitro approach we further demonstrate that IgM inhibits LPS-induced maturation of myeloid dendritic cells, as well as LPS-induced activation of NF-κB and the expression of proinflammatory cytokines such as TNF-α, IL-12, and IFN-β. In conclusion, we propose that immature dendritic cells are key factors in liver granulomas and that the commonly observed hyper-IgM may contribute to their appearance in patients with PBC.